Social responsibility and reflexivity for co‐operative goals with government units in China. (7th May 2015) - Wong, Alfred; Snell, Robin; Tjosvold, Dean
Abstract : Prior research on co‐operation and competition has established that co‐operative goal relationships with government units are beneficial to business enterprises operating in China. We report a quantitative study, conducted in Shanghai and based on 119 paired responses by government officials and business managers, which sought to establish the antecedents of co‐operative business–government goal relationships. We found that business enterprises in China that were represented by managers with favorable attitudes toward ethics and social responsibility were considered by government officials as more inclined to engage in reflexivity, i.e. to hold open discussions with them about organizational objectives and procedures, with a view to mutual adjustment and improvement. Greater reflexivity was, in turn, more likely to lead to business–government relationships based on co‐operative rather than independent or competitive goals. Given the considerable importance of business–government relationships in China, these findings imply that concern for corporate social responsibility (CSR) may be advantageous for firms there, and we discuss how the HRM function may contribute to development of suitable CSR policies, projects and practices, to greater reflexivity, and to the increased likelihood of establishing co‐operative goals. Key points: Co‐operation with government units has benefitted businesses in China. Business representatives who supported CSR engaged in reflexivity with government officials, which the latter saw as a path toward developing co‐operative goals. The HRM function can help strengthen CSR commitment and reflexivity skills among business managers.